High-performance asymmetric supercapacitor based on graphene hydrogel and nanostructured MnO2 - Gao, Hongcai (2013)
We have successfully fabricated an asymmetric supercapacitor with high energy and power densities using graphene hydrogel (GH) with 3D interconnected pores as the negative electrode and vertically aligned MnO2 nanoplates on nickel foam (MnO2-NF) as the positive electrode in a neutral aqueous Na2SO4 electrolyte. Because of the desirable porous structure, high specific capacitance and rate capability of GH and MnO2-NF, complementary potential window of the two electrodes, and the elimination of polymer binders and conducting additives, the asymmetric supercapacitor can be cycled reversibly in a wide potential window of 0–2.0 V and exhibits an energy density of 23.2 Wh kg–1 with a power density of 1.0 kW kg–1. Energy density of the asymmetric supercapacitor is significantly improved in comparison with those of symmetric supercapacitors based on GH (5.5 Wh kg–1) and MnO2-NF (6.7 Wh kg–1). Even at a high power density of 10.0 kW kg–1, the asymmetric supercapacitor can deliver a high energy density of 14.9 Wh kg–1. The asymmetric supercapacitor also presents stable cycling performance with 83.4% capacitance retention after 5000 cycles.